2021
DOI: 10.3389/fcell.2021.766205
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Attenuates Hepatic and Intestinal Injuries and Modulates Gut Microbiota and Gene Expression Profiles in Mice Infected with Schistosoma japonicum

Abstract: Parasitic infection can induce pathological injuries and impact the gut microbiota diversity and composition of the host. Bacillus subtilis is a nonpathogenic and noninvasive probiotic bacterium for humans and other animals, playing an important role in improving the host immune system’s ability to respond to intestinal and liver diseases and modulating gut microbiota. However, whether B. subtilis can impact biological functions in Schistosoma japonicum–infected mice is unclear. This study used oral administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…The previous study has revealed that S. japonicum infection could induce alteration of gut microbiota in mice ( 29 ). In this study, Bacteroidetes and Firmicutes were the dominant phyla in mice ( Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The previous study has revealed that S. japonicum infection could induce alteration of gut microbiota in mice ( 29 ). In this study, Bacteroidetes and Firmicutes were the dominant phyla in mice ( Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate specific diagnostic biomarkers of schistosomiasis, we compared the difference in the gut microbiota of mice infected with non-pathogenic factors and pathogenic S. japonicum . Previous studies have shown that probiotic Bacillus subtilis could affect the composition of gut microbiota and the level of liver disease in mice ( 29 , 39 , 40 ). Here, we showed that gut microbiota diversity and structure of gut microbiota of mice treated with Bacillus subtilis (non-pathogenic factor) significantly differed from these of mice infected with S. japonicum using Shannon index ( Figure S4A ) and PLS-DA analysis ( Figure S4B ), and the diversity of gut microbiota of mice treated with Bacillus subtilis is significantly higher than that of S. japonicum- infected group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations